Microwave Observations of Ganymede's Sub‐surface Ice: 2. Reflected Radiation - Zhimeng Zhang; Shannon Brown; Scott Bolton; Steven Levin; Virgil Adumitroaie; Lea E. Bonnefoy; Jianqing Feng; Paul Hartogh; Jonathan Lunine; Sidharth Misra; Matthew Siegler (Geophysical Research Letters, 2023)
Abstract Juno's microwave radiometer experiment (MWR) provided the first spatially resolved observations beneath the surface of Ganymede's ice shell. The results indicate that scattering is a significant component of the observed brightness temperature, which is a combination of the upwelling ice emission and reflected emission from the sky and from Jupiter's synchrotron emission (Brown et al., 2023). Retrieval of the sub‐surface ice temperature profile requires that these confounding signals are estimated and removed to isolate the thermal signature of the ice. We present data analysis and model results to estimate the reflected synchrotron emission component. Our results indicate reflected emission over a broad range of observed angles, due to surface roughness and internal scattering. Based on viewing geometry, direct specular reflection from a smooth surface at a narrow angle is not observed. A microwave‐reflective medium is indicated, that is, a very rough surface and/or non‐homogeneous subsurface.